Genome sequence of the acid-tolerant Burkholderia sp. strain WSM2230 from Karijini National Park, Australia. Issue 3 (November 2014) - Walker, Robert; Watkin, Elizabeth; Tian, Rui; Bräu, Lambert; O'Hara, Graham; Goodwin, Lynne; Han, James; Lobos, Elizabeth; Huntemann, Marcel; Pati, Amrita; Woyke, Tanja; Mavromatis, Konstantinos; et al.
Abstract Burkholderia sp. strain WSM2230 is an aerobic, motile, Gram-negative, non-spore-forming acid-tolerant rod isolated from acidic soil collected in 2001 from Karijini National Park, Western Australia, usingKennedia coccinea (Coral Vine) as a host. WSM2230 was initially effective in nitrogen-fixation withK. coccinea, but subsequently lost symbiotic competence. Here we describe the features ofBurkholderia sp. strain WSM2230, together with genome sequence information and its annotation. The 6, 309, 801 bp high-quality-draft genome is arranged into 33 scaffolds of 33 contigs containing 5, 590 protein-coding genes and 63 RNA-only encoding genes. The genome sequence of WSM2230 failed to identify nodulation genes and provides an explanation for the observed failure of the laboratory grown strain to nodulate. The genome of this strain is one of 100 sequenced as part of the DOE Joint Genome Institute 2010 Genomic Encyclopedia for Bacteria andArchaea -Root NoduleBacteria (GEBA-RNB) project.